The Impact of Technological Innovations on Employment in Manufacturing Sector: A Case of Pakistan Economy (Journal of Asian Development Studies, 2025)
This paper explores the impacts of technological advancement in the manufacturing sector in Pakistan’s economy especially the information and communication technology (ICT) facilities. Using time series data and vector auto regression (VAR) analysis, this paper also analyses the dynamics of employment, technology and investment in a given time frame. Based on the importance of technological innovations, the study seeks to investigate the impact of technological innovations in Pakistan from 1995 to 2023.So, data from 1995-2023 was used to analyzed the model. The results reveal that the positive gains arising from ICT improvements are substantially unfavorable to employment and investment, primarily because of the adverse employment impacts from automation. Although the level of contribution by capital has been low in the achievement of employment and ICT is still the most dominant factor in growth. The result of the analysis is that the employment increases continuously even with the slowing down of both the ICT and investment which has long-term implication on the sector. In light of this, the current study offers a full perspective on how the enhancement of technology impacts on labor and capital procurement within the manufacturing sector of Pakistan. Study also reveals positive effects of ICT on employment were dependent on how skilled the workers were. And in the regions with low employment of that kind of skill, the advantages of more ICTs were limited and even led to downsizing of workforce rather than exploiting further utilization of workforce.